Tactics of Assistance – Important Condition of Teaching Independence of the Primary School Pupils - Holub, Olena (Pedagogical Discourse, 2015)
The article analyzes the practice of education independence for primary school pupils and study conditions for the use of assistance strategy in the education of the personality traits. It is concluded that in the upbringing of independence, adults’ educational efforts should be directed to the inner world of the child and used support pedagogy aimed at developing the uniqueness of the child, on the formation of its author’s position in life support for his independence and adulthood. It is noted that the modern elementary school teacher should be able to use a variety of tactics of interaction with the child, and especially strategy of help analyses of the content of which in each case contributes to determine the level of education of the student independence and enables the development of effective educational interventions that provide individual attention to each pupil.